2019
DOI: 10.36380/scil.2019.wvj38
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Aloe vera, Apium graveolens and Sauropus androgynus Alcoholic Extracts against Methicillin-Resistant Staphylococcus aureus.

Abstract: Staphylococcus aureus is a Gram-positive bacteria that influence human health. Staphylococcus aureus becomes a more serious problem if it is resistant to methicillin. This phenomenon is known as methicillin-resistant Staphylococcus aureus (MRSA). This study aimed to elucidate the chemical compounds, antioxidant activity and efficacy of Aloe vera (AV), Apium graveolens (AG), Sauropus androgynus (SA) extracts and its combinations against MRSA. All the herbs were extracted and determined its antioxidant constitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…This study demonstrated that MRSA has a high resistance profile against AMP, as reflected by the high concentration of AMP (1024 µg/ mL) on the inhibition of MRSA growth. Conversely, SAE inhibited MRSA at a concentration of 2 mg/mL, which was similar to that of a previous study [20]. The combination of SAE+AMP induced stronger bacteriostatic activity, which was supported by a decreased concentration of SAE+AMP to 0.5 mg/mL+4 µg/mL for MRSA inhibition, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…This study demonstrated that MRSA has a high resistance profile against AMP, as reflected by the high concentration of AMP (1024 µg/ mL) on the inhibition of MRSA growth. Conversely, SAE inhibited MRSA at a concentration of 2 mg/mL, which was similar to that of a previous study [20]. The combination of SAE+AMP induced stronger bacteriostatic activity, which was supported by a decreased concentration of SAE+AMP to 0.5 mg/mL+4 µg/mL for MRSA inhibition, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Celery exhibits several potential benefits against MRSA due to its biochemical content. A previous study described that celery contains alkaloids, flavonoids, phenolic compounds, saponins, and tannins [ 7 ]. Phenolic compounds are the highest biochemical content of celery extract.…”
Section: Discussionmentioning
confidence: 99%
“…J01XA01, Amarox Pharma Global, Indonesia] per kg body weight [BW]) [ 11 ], Group P1 (infected with MRSA+1 mg celery extract per kg BW), Group P2 (infected with MRSA+2 mg celery extract per kg BW), and Group P4 (infected with MRSA+4 mg celery extract per kg BW). The celery extract doses were selected following a previous study [ 7 ]. MRSA infection was induced by intraperitoneal injection of 50 mL of 1.0 McFarland standard bacterial suspension.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations